Building information modeling (BIM) adoption among Libyan construction organizations : the moderating effect of organizational culture - Mohamed Ghayth Farhat, Elghdban (2023)
Building Information Modelling (BIM) is well-known in the construction sector as an important tool for improving organizational performance. In this sense, worldwide BIM adoption is rapidly expanding, however this new phenomenon is not growing at the same rate as in Libya. Despite the fact that BIM has been existed for over 20 years, construction organizations in Libya are still struggling to adopt integrated BIM technology. Although previous studies have looked at the factors that influence technology adoption, there are still crucial concerns that have not been completely investigated and must be addressed. They include: (1) Previous research on the factors that influence BIM adoption has yielded inconclusive results. As a result, further study is needed to investigate potential moderators in the processes of a firm experiencing, interpreting, and controlling internal and external important factors. Investigating the moderating influence of organizational culture may assist in resolving inconsistencies in prior studies. (2) Despite BIM processes requiring organization-wide adoption, However only few study sought to integration of variables of the most important theories at organisations level such as TOE , DOI and INT, the constructs of these of theories have not clearly identified the factors that influence BIM adoption in construction organisations , especially in Libya construction organisations. As a result, the aim of this study is to close these gaps by identifying the variables impacting BIM technology adoption in Libya. Organizational culture has been applied to understand the moderating effect between influential factors and BIM adoption. An integrated research model was constructed based on the Technology Organization Environment (TOE) theory to explain the relative effect of seven known factors. The information was gathered through a survey of 411 Libyan construction organization. PLS-SEM (Partial Least Squares-Structural Equation Modelling) was used to analyse the data, evaluate the measurement and structural model, and test the hypotheses. According to the data, Libyan construction enterprises are not technological sophisticated, and they continue to use common technologies such as 2D CAD. The path analysis results demonstrated that the technological factors (Perceived Relative Advantage and Compatibility) related positively to BIM adoption, while Complexity related negatively to BIM adoption. Organizational factors (top management support) also related positively with environmental factors (Coercive Pressure) on the adoption of BIM. Organizational culture was also found to have a moderating effect on the relationship between environmental factors (Normative pressure) and the adoption of BIM in Libyan construction organizations. The study's findings provide significant insight into important factors that might increase the level of BIM adoption. In summary, the integration of the research model gave a comprehensive explanation for BIM adoption in organizations. The adoption of BIM could serve as a base for future research in other emerging technology adoptions in organizations.